Frailty syndrome - symptoms and diagnosis. - Paula Jankowska; Krzysztof Jankowski; Ewa Rudnicka-Drożak (Kazimierz Wielki University, 2018)
Introduction Nowadays, systematic increase in the share of older people in the community around the world is described. In elderly some characteristic health problems are observed. One of them is frailty syndrome. Objective The objective of this work is to present symptoms of frailty syndrome and ways of its diagnosis. Results There is an emerging evidence that such health problems as heart failure, chronic obstructive pulmonary disease and renal failure may contribute to frailty syndrome development. Most widely used definition of frailty, delineates it as a state of increased vulnerability from age-associated decline in reserve and function resulting in reduced ability to cope with everyday or acute stressors. According to consensus of medical societies, all persons aged 70 years and older should be involved in the group in which screening for frailty is performed by healthcare providers Conclusions With severe life-threatening consequences, frailty is considered as a condition that should be included in the elderly screening program. There are many instruments used for frailty screening. In primary healthcare clinical setting the most practical are brief and accurate tools, assessing multidirectional issue of frailty. These criteria are to the highest extend fulfilled by the Tilburg Frailty Index, the Groningen Frailty Indicator and the Gérontopôle Frailty Screening Tool.